Polarization dependence of non-linear gain compression factor in semiconductor optical amplifier - Bradley, Louise (My University, 2008)
We investigate the power and the polarization dependence of the intraband dynamics in a bulk semiconductor optical amplifier using both a 2.5-ps pump-probe experimental set-up in contra-propagation and a theoretical model. Our model is based on the rate equations and takes into account the polarization dependence of the gain. By comparing experimental and computational results we are able to highlight the dependences of the intraband dynamics and to extract the non-linear gain compression factor as a function of both pulse energy and polarization of the injected pulses.
PUBLISHED
Keywords: Optoelectronics; Semiconductor Optical Amplifier